Preclinical and Predictive Algorithms in Monitoring Patients with Autoimmune Diseases and Their Relatives-at-Risks - Suchkov, Sergey; Kostyushev, Dmitry; Gnatenko, Dmitry; Gadzhieva, Sevindzh; Paltsev, Mikhail (IntechOpen, 2011)
None